2008
DOI: 10.1002/jts.20315
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of anger and treatment outcome in combat veterans with posttraumatic stress disorder

Abstract: Research has identified anger as prominent in, and an influence on, treatment outcome for military veterans with posttraumatic stress disorder (PTSD). This study examined factors influencing the relationship between anger and outcome to improve treatment effectiveness. Participants comprised 103 veterans attending PTSD treatment. Measures of PTSD and comorbidity were obtained at intake and 9-month follow-up. Measures also included potential mediators of therapeutic alliance, social support, problematic/undermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 22 publications
(25 reference statements)
8
120
0
Order By: Relevance
“…That Veterans may be hesitant to experience anger is not surprising given that Veterans often report that anger is the problem that interferes most with functioning [27]. Importantly, in their recent study, Forbes et al found that fear of anger (that is, the extent to which an individual is fearful of experiencing their own anger because of possible negative consequences), in addition to alcohol-related comorbidity, mediated the association between anger severity and PTSD treatment outcome [26]. Such findings provide further understanding of the effect that anger can have on the effectiveness of PTSD treatments and elucidates the specific anger-related factors involved, namely a fear of experiencing this emotion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…That Veterans may be hesitant to experience anger is not surprising given that Veterans often report that anger is the problem that interferes most with functioning [27]. Importantly, in their recent study, Forbes et al found that fear of anger (that is, the extent to which an individual is fearful of experiencing their own anger because of possible negative consequences), in addition to alcohol-related comorbidity, mediated the association between anger severity and PTSD treatment outcome [26]. Such findings provide further understanding of the effect that anger can have on the effectiveness of PTSD treatments and elucidates the specific anger-related factors involved, namely a fear of experiencing this emotion.…”
Section: Methodsmentioning
confidence: 99%
“…How might anger affect such outcomes? As noted by Forbes et al, there may be several ways, including the possibility that anger may negatively affect the therapeutic alliance or that individuals may be afraid to access fear-relevant memories because doing so may activate their anger and trigger attack behaviors [26]. That Veterans may be hesitant to experience anger is not surprising given that Veterans often report that anger is the problem that interferes most with functioning [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the present analysis was cross-sectional in nature and thus we are unable to establish whether anger problems developed after PTSD or whether anger problems pre-existed exposure to trauma or the development of PTSD. As there is some question in the literature about the temporality of how anger problems impact the phenomenology of PTSD (Andrews, Brewin, Rose, & Kirk, 2000;Andrews, Brewin, Stewart, Philpott, & Hejdenberg, 2009;Ehlers, Mayou, & Bryant, 1998Feeny, Zoellner, & Foa, 2000;Forbes et al, 2008;Hawkins & Cougle, 2011;Koenen, Stellman, Stellman, & Sommer, 2003;McHugh, Forbes, Bates, Hopwood, & Creamer, 2012), it would be useful to follow a military cohort to assess pre-trauma anger levels and to ascertain trajectories of anger response and PTSD symptomatology over time.…”
Section: Discussionmentioning
confidence: 99%
“…Anger problems are associated with a number of negative consequences including poor family functioning (Evans, McHugh, Hopwood, & Watt, 2003;Taft, Schumm, Panuzio, & Proctor, 2008), negative workplace and school outcomes (Chen & Spector, 1992;Frueh, Henning, Pellegrin, & Chobot, 1997;Hershcovis et al, 2007;Inness, Leblanc, & Barling, 2008;O'Neill, Vandenberg, Dejoy, & Wilson, 2009;Struthers, Miller, Boudens, & Briggs, 2001; S. P. Thomas & Smith, 2004), aggression (Taft, Street, Marshall, Dowdall, & Riggs, 2007;Teten et al, 2010), and poorer treatment outcomes for posttraumatic stress disorder (PTSD) (Forbes et al, 2005; Creamer, Hawthorne, Allen, & McHugh, 2003;Forbes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%